PERKEMBANGAN PERATURAN MENGENAI REDISTRIBUSI TANAH DALAM RANGKA REFORMA AGRARIA DI KABUPATEN BOYOLALI - Mujiati Mujiati; Nuraini Aisiyah (BHUMI: Jurnal Agraria dan Pertanahan, 2014)
Land Redistribution is one of the efforts to reduce the inequality of land tenure and ownership, especially for tenantsand small farmers. The regulations stipulated in the Government Regulation No. 224, the year 1961 related to the objects ofredistribution must be suited to the reality of development in which the land is no longer available. This needs the guidelinesto implement. In 2013. the Directorate of Land Reform of the BPN RI issued guidelines of land redistribution which was in linewith the similar government regulations. In Musuk subdistrict, Boyolali Regency, the implementation of land redistributionsuited the technical operation of 2013. Those having the right to receive were elligible as required in Article 8 and 9 of theGovernment Regulation No. 224 of 1961. In order to optimize the production and income of the land beneficiaries, the landreceivers need to form an as a breakthrough for land/access to obtain the capital.Keywords : Land Redistribution, object and subject of redistribution.